2009
DOI: 10.1093/sw/54.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Older Adult Inmates: The Challenge for Social Work

Abstract: Older adult inmates have grown both in proportion and in number due to the confluence of a number offactors. This aging of the prison population has created a host of policy and practice issues that encompass justice considerations, cost containment issues, and biopsychosocial care needs. The older prisoner's physical, social, and psychological needs are complex and necessitate gerontologically based service delivery systems. The intent of this article is to help in the preparation of social work practitioners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 7 publications
(2 reference statements)
0
41
0
Order By: Relevance
“…19,28, 47 Hayes et al 20 conducted the most recent study regarding older prisoners' social care needs, reporting that accommodation was the most commonly unmet need. Further evidence for a lack of appropriate and timely support with housing was provided by Senior et al, 27 whose findings revealed that older prisoners were frequently unaware of where they were going to be living in the community in the months, weeks and even days prior to release.…”
Section: Social Care Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,28, 47 Hayes et al 20 conducted the most recent study regarding older prisoners' social care needs, reporting that accommodation was the most commonly unmet need. Further evidence for a lack of appropriate and timely support with housing was provided by Senior et al, 27 whose findings revealed that older prisoners were frequently unaware of where they were going to be living in the community in the months, weeks and even days prior to release.…”
Section: Social Care Needsmentioning
confidence: 99%
“…47 Hayes et al 7 found that over one-third of older prisoners in their sample had some level of functional need in activities of daily living (ADL), with 11% having personal care needs, in over half of whom they were unmet. A US study 48 explored prison activities of daily living (PADL) in 120 female prisoners aged > 55 years.…”
Section: Social Care Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing a seamless bridge between prison and community is not only a key component of providing individual, family, and community cohesion, health and well-being (Snyder et al, 2009), it may also be key to reducing the $60 billion in reentry costs that are positioned to increase as more prisoners age with complex health and social care needs (Nunez-Neto, 2008). The promising programs highlighted in this chapter suggest that even correctional staff can overcome over attitudinal and systemic barriers to treat incarcerated aging people and their families with dignity and respect and help make communities safer.…”
Section: Future Directionsmentioning
confidence: 99%
“…Regardless of personal views on releasing aged, infirm prisoners, the reality is that correctional settings are overcrowded as well as cash strapped, and selective decarceration has been proposed by some as an approach to dealing with prison overcrowding and the considerable cost of caring for old and infirm inmates who no longer pose a threat to others (Kerbs, 2000;Snyder, van Wormer, Chadha, & Jaggars, 2009). In fact, prison officials have "begun to recognize that older offenders might be better candidates for early release because of their low recidivism rates" as compared to young offenders (Snyder et al, 2009, p. 121).…”
mentioning
confidence: 99%